Case Report: Targeted treatment by fluoxetine/norfluoxetine of a KCNC2 variant causing developmental and epileptic encephalopathy - Ping Li; Alice Butler; Yu Zhou; Karl L. Magleby; Christina A. Gurnett; Lawrence Salkoff (Frontiers in Pharmacology)
The Kv3.2 subfamily of voltage activated potassium channels encoded by the KCNC2 gene is abundantly expressed in neurons that fire trains of fast action potentials that are a major source of cortical inhibition. Gain-of-function (GOF) de novo pathogenic variants in KCNC1 and KCNC2, encoding Kv3.1 and Kv3.2 respectively, cause several types of epilepsy including developmental and epileptic encephalopathy (DEE). Fluoxetine (Prozac) is a known inhibitor of the Kv3.1 current and was reported to improve seizure control in a single patient with a KCNC1 GOF variant. Here, we describe fluoxetine treatment of two siblings with a de novo KCNC2 V473A variant associated with DEE, which resulted in improved seizure control, ability to wean antiepileptic medications, and improved development. The KCNC2 V437A variant showed GOF activity as demonstrated by HEK293 cells expressing variant subunits activating at more hyperpolarized potentials than WT channels. Fluoxetine reduced currents equally for both Kv3.2 WT and Kv3.2-V473A variant channels, with an IC50 of ∼12 µM. Further analysis of this repurposed drug showed that norfluoxetine, a long-lasting metabolite of fluoxetine which is produced in the liver and accumulates in the brain, was more effective than fluoxetine itself in selectively inhibiting the dominant pathogenic channel activity of the pathogenic allele. Norfluoxetine showed 7-fold greater selectivity in inhibiting Kv3.2 variant currents (IC50 of ∼0.4 µM) compared to WT currents (IC50 of ∼2.9 µM). Combined with a previous report of improved outcomes for a KCNC1 variant, our results suggest that fluoxetine or its metabolite, norfluoxetine, may be beneficial for patients with GOF variants in KCNC2 and other neuronal potassium channels.